CORRELATIONS BETWEEN MEDICAL-ECONOMIC AND EPIDEMIOLOGICAL RATES WITH THE FREQUENCY OF TREATMENT DEFAULTS IN TUBERCULOSIS PATIENTS - I. M. Son; D. D. Pashkevich; S. A. Sterlikov; I. D. Danilova; A. V. Dergachyov; D. A. Kucheryavaya (Туберкулез и болезни лёгких)
The article describes the results of the correlation analysis of the standardized rate of treatment defaulters and rates reflecting the interaction between the doctor and the patient, medical and economic rates and the rates reflecting the tuberculosis epidemic situation. The correlation has been found between the part of treatment defaulters and the number of doctors per one patient and regularity of the meetings of the doctor and patients, tuberculosis mortality rates, prevalence of tuberculosis with bacillary excretion, rate of reduction in the prevalence of multiple drug resistant tuberculosis and the number of rates reflecting the treatment efficiency. No correlation has been found between the part of patients defaulting from treatment with medical and economic rates, incidence, frequency of relapses and primary multiple drug resistance. Reduction of the part of treatment defaulters will promote the implementation of the tasks of the Russian state health care policy.